Peran Pondok Pesantren dalam Mengentaskan Kenakalan Santri: Studi Kasus Pondok Pesantren Al-Ikhlas Al-Islamy Kaliaji Desa Monggas - Zihniatul Ulya; Ulya, Zihniatul; Abubakar, Mujahidin; Hidayatullah, Lalu Diraja (Mahad Aly Al Fithrah, 2024)
Delinquency in teenagers is a very important thing to discuss, especially recently, which we have witnessed in various places through social media or other news media. Negative consequences arise that are so worrying that they will bring destruction to teenagers themselves and society in general. This makes Islamic boarding schools an alternative business for looking after teenage children. The aim of this research is to determine the forms of delinquency among students at the al-Ikhlas al-Islamy Kaliaji Islamic boarding school and the role of Islamic boarding schools in alleviating student delinquency at the al-Ikhlas al-Islamy Kaliaji Islamic boarding school, Monggas village. The method used in this research is a qualitative research method, with the type of research the author uses is a case study. The data collection techniques were carried out using observation methods, interview methods and documentation methods. The subjects in this research were Islamic boarding school leaders, dormitory administrators and teachers at the Al-Ikhlas Al-Islamy Kaliaji Islamic boarding school, Monggas village. From the results of this research, it can be seen that the forms of delinquency of the students of the al-Ikhlas al-Islamy Kaliaji Islamic Boarding School. The forms of delinquency committed by the students of the al-Ikhlas al-Islamy Kaliaji Islamic Boarding School, namely running away (running away from the Islamic boarding school) and playing truant, dressing not in accordance with the regulations. madrasas, carrying cell phones and breaking the language, fighting between students or bullying each other, smoking and borrowing without permission. The role of the Al-Ikhlas Al-Islamy Kaliaji Islamic Boarding School in Monggas village in alleviating student delinquency is to carry out several actions and policies that have been created, then direct the students to use every free time they have for positive things by taking part in the extracurricular activities that have been established. Islamic boarding school is provided.